2006
DOI: 10.1002/j.1681-4835.2006.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ICT on Organizations in Tunisia

Abstract: Under economic and technological changes, companies become more conscious of the importance of their structures, technologies and intellectual capital. The progress made in information and communication technologies (ICT) allows for storage and fast circulation of information. Indeed the communication networks supported by the various existing applications such as the electronic messaging, the teleconferences, and the groupware are drawing up the foundations of a new community which does not have the same temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This, to some extend, has also been supported empirically (see for example, Prasad, 2008a). At national level, Ziadi and Kuofie (2006) found that in Tunisia, businesses are not yet completely committed to the revolution of the information. They suggest that this lack of initiative could be because new technologies require investments, including development of human resources, which the Tunisian businesses do not feel ready to provide.…”
Section: It Investments and Their Benefits In Developing Countriesmentioning
confidence: 63%
“…This, to some extend, has also been supported empirically (see for example, Prasad, 2008a). At national level, Ziadi and Kuofie (2006) found that in Tunisia, businesses are not yet completely committed to the revolution of the information. They suggest that this lack of initiative could be because new technologies require investments, including development of human resources, which the Tunisian businesses do not feel ready to provide.…”
Section: It Investments and Their Benefits In Developing Countriesmentioning
confidence: 63%
“…There are numerous, both theoretical and empirical, confirmations that support this claim [3], [8], [34]. It has been proven that ICT leads to information processing cost reduction, decision-making quality improvement, decrease in the number of hierarchical levels and organization "thinning", and also to decrease in middle-level management.…”
Section: Introductionmentioning
confidence: 92%
“…Organizations require fast Internet speed so as to save on time as well as enhance productivity and efficiency. Fast Internet speed is needed to support multiple users (Ziadi & Knufie, 2016).…”
Section: Internet Speed and Service Deliverymentioning
confidence: 99%